ANÁLISE DE CONTEÚDOS DE FÍSICA MODERNA E CONTEMPORÂNEA EM LIVROS DIDÁTICOS DE FÍSICA DO ENSINO MÉDIO DA REDE PÚBLICA ESTADUAL DE SÃO LUÍS-MA. - PEREIRA, Patrícia do Nascimento (2019)
This work aimed to analyze the quality of how the contents of Modern and Contemporary Physics (FMC) are proposed in high school Physics Textbooks (LD) approved by the National Textbook Program (PNLD) of 2018 and chosen by three public schools of the city of São Luís-MA. To this end, the objective was (1) to describe the contents of FMC and to discuss its relevance in the student’s scientific and citizen formation and (2) to analyze the degree of presence of the processes of historical / socio-cultural contextualization, illustration/exemplification, daily and critical. In the development of this research, the qualitative approach and the documentary typology were used. The Physics LDs were acquired in three state public schools of São Luís and analyzed from the perspective of Bardin’s Content Analysis (2011). The analysis of the LD of Physics took place on two fronts. In the first, it was found that all the books analyzed presented FMC contents, but what differs them is the organization of these contents, being possible to notice that there are books that target more topics than the others. It was also verified the presence of two central themes, Relativity Theory and Quantum Physics. This is explained by the notoriety of the impacts that this knowledge has been producing on society. Still, on the first front, the topics were absent photoelectric effect and nanotechnology in two LD. The second work front corresponds to the analysis of the theoretical body of contents against the perspective of contextualization. The data showed that only two LD present the historical/socio-cultural contextualization satisfactorily, besides, the illustration/exemplification contextualization is the most used by the LD in the approach of the scientific contents. It was evident that the everyday contextualization process is infrequently presented in the analyzed books and the perspective of critical contextualization is presented only once, superficially and only in one book. With this, we conclude that the lack of critical approach in LD makes the process of Scientific and Technological Literacy difficult. Being one of the main objectives of Physics Education in basic education should be to train citizens who can fully experience citizenship, developing skills and abilities to position themselves in front of social and environmental issues critically and reflectively.